Work–Life Balance, Job Stress, and Turnover Intention: The Mediating Role of Job Satisfaction at PT Global Kriya Nusantara - Ramdani, Rina; Hermina, Nurul (Dinasti Publisher, 2025)
This study aims to analyze the influence of Work–Life Balance and Job Stress on Turnover Intention with Job Satisfaction as a mediating variable among employees of PT Global Kriya Nusantara. The research problem arises from increasing work demands and production pressures that affect employees’ working conditions and their balance between professional and personal life. This study employs a quantitative approach and involves 157 respondents selected through a census technique. Data were analyzed using Covariance Based-Structural Equation Modeling (CB-SEM). The results show that Work–Life Balance significantly influences Job Satisfaction, and Job Stress also has a significant influence on Job Satisfaction. Work–Life Balance further demonstrates a significant influence on Turnover Intention, and Job Stress likewise exerts a significant effect. In addition, Job Satisfaction acts as a significant mediating variable in the relationships between Work–Life Balance and Job Stress toward Turnover Intention. These findings highlight the importance of strengthening work–life balance initiatives and effectively managing job stress to enhance job satisfaction and support organizational stability.